Immunohistochemical assessment of epidermal growth factor receptor and prohibitin expression in “post-COVID” placentas: results of a comparative cross-sectional study - G.S. Manasova; Y.O. Stasii (Репродуктивная эндокринология)
Background. COVID-19 pandemic is accompanied by a considerable number of morbidity cases among pregnant women. Certain knowledge has been accumulated about the histopathological features of the placenta during SARS-CoV-2 infection. Specific proteomic studies of the function of the placenta are insufficient. Objective of the study: to study the perinatal outcomes of pregnancy and histopathological features of the placenta and the expression of epidermal growth factor receptors (EFGR) and prohibitin (PHB) in the placenta in pregnant women with COVID-19 infection in comparison with data in a group of healthy pregnant women without a COVID-19 history. Materials and methods. 58 pregnant women with COVID-19 infection during pregnancy and 40 healthy pregnant women were examined at the base of Maternity Hospital No. 2 of the Odessa City Council. A histological and immunohistochemical study of placentas was carried out for the expression of EFGR and PHB In addition to a general clinical examination. Results. A higher frequency of premature births (15.51% vs 5%) and cesarean sections (34.4% vs 12.5%) in the “post-COVID” group was revealed. Most women fell ill in the third trimester of pregnancy (65.51%). A significant difference was found in Apgar scores in the groups (6.48 ± 2.39 vs 8.05 ± 0.54 points), in the weight of newborns (3067.93 ± 620.21 g vs 3617.25 ± 354.58 g). In the placentas of the “post-COVID” group, signs of mother’s (53.45% vs 12.5%) and fetus’ vascular malperfusion (32.7% vs 15%) were detected with greater frequency; as well as hemodynamic disturbances (53.45% vs 15%). Analysis of EFGR expression in the groups showed no differences (2.96 ± 0.2 vs 2.75 ± 0.44) in contrast to PHB (1.52 ± 1.12 vs 0.25 ± 0.5), which was characterized by overexpression in the women with COVID-19. Conclusions. SARS-CoV-2 infection during pregnancy is associated with certain changes in placental metabolism, and changes in the expression of placental proteins EGFR and PHB may be involved in the pathogenetic mechanisms of the placental dysfunction development. The limited sample size requires additional research.